Enhancing Elementary Students’ Science Achievement through the Snowball Throwing Model with Visual Cue Cards: A True Experimental Study - Ahmad Muzari; Akhsanul In'am; Dyah Worowirastri Ekowati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study investigated the effectiveness of integrating the Snowball Throwing cooperative learning model with visual cue cards in improving elementary students’ science achievement on ecosystem concepts. The study employed a true experimental pretest–posttest control group design involving 66 fifth-grade students randomly assigned to experimental and control groups. Student achievement was measured using a validated multiple-choice test. Prior to hypothesis testing, data met parametric assumptions, as indicated by normal distribution (Shapiro–Wilk, p > .05) and homogeneous variance (Levene’s test, p = .651). Data were analyzed using independent samples t-tests and effect size estimation. The results revealed that the experimental group achieved significantly higher posttest scores than the control group (t(64) = 6.12, p < .001), with a large effect size (Cohen’s d = 1.46). Gain score analysis also showed a significant difference (t(64) = 7.22, p < .001; Cohen’s d = 1.80), indicating substantially greater learning improvement among students exposed to the cooperative–visual approach. These findings suggest that combining structured peer interaction with visual scaffolding effectively enhances conceptual understanding in elementary science learning. The study provides empirical support for implementing multimodal cooperative strategies to improve science achievement in primary education. Keywords: cooperative learning, elementary education, science achievement, snowball throwing, visual cue cards